Antioxidant and Anti-Inflammatory Activities in Extracts from Minke Whale (Balaenoptera acutorostrata) Blubber - Mari Johannessen Walquist; Svein Kristian Stormo; Ida-Johanne Jensen; Bjarne Østerud; Karl-Erik Eilertsen (Mediators of Inflammation)
Intake of long-chain omega-3 polyunsaturated fatty acids (LC-n3-PUFA) is commonly recognized to reduce cardiovascular disease (CVD). In previous studies, cold-pressed whale oil (CWO) and cod liver oil (CLO) were given as a dietary supplement to healthy volunteers. Even though CWO contains less than half the amount of LC-n3-PUFA of CLO, CWO supplement resulted in beneficial effects on anti-inflammatory and CVD risk markers compared to CLO. In the present study, we prepared virtually lipid-free extracts from CWO and CLO and evaluated the antioxidative capacity (AOC) and anti-inflammatory effects. Oxygen radical absorbance capacity (ORAC) and ferric reducing antioxidant power (FRAP) assays were used to test the AOC, and the results indicated high levels of antioxidants present in all extracts. The anti-inflammatory effects of the extracts were tested with lipopolysaccharide- (LPS-) treated THP-1 cells, measuring its ability to reduce cytokine and chemokine secretion. Several CWO extracts displayed anti-inflammatory activity, and a butyl alcohol extract of CWO most effectively reduced TNF-α (50%, p<0.05) and MCP-1 (85%, p<0.001) secretion. This extract maintained a stable effect of reducing MCP-1 secretion (60%, p<0.05) even after long-term storage. In conclusion, CWO has antioxidant and anti-inflammatory activities that may act in addition to its well-known LC-n3-PUFA effects.